2020
DOI: 10.1038/s41598-020-73828-0
|View full text |Cite
|
Sign up to set email alerts
|

Energy band alignment at the heterointerface between CdS and Ag-alloyed CZTS

Abstract: Energy band alignment at the heterointerface between CdS and kesterite Cu2ZnSnS4 (CZTS) and its alloys plays a crucial role in determining the efficiency of the solar cells. Whereas Ag alloying of CZTS has been shown to reduce anti-site defects in the bulk and thus rise the efficiency, the electronic properties at the interface with the CdS buffer layer have not been extensively investigated. In this work, we present a detailed study on the band alignment between n-CdS and p-CZTS upon Ag alloying by depth-prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 41 publications
2
26
0
2
Order By: Relevance
“…Figure shows the valence band spectra of the leaf structure of CdS measured at different take-off angles. The data obtained at the take-off angle of 0° show that the main Cd 4d peak appears at 11.2 eV, which matches with the reported data of CdS . In addition, we observed that a shoulder appeared at higher binding energy.…”
Section: Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Figure shows the valence band spectra of the leaf structure of CdS measured at different take-off angles. The data obtained at the take-off angle of 0° show that the main Cd 4d peak appears at 11.2 eV, which matches with the reported data of CdS . In addition, we observed that a shoulder appeared at higher binding energy.…”
Section: Results and Discussionsupporting
confidence: 91%
“…The data obtained at the take-off angle of 0°show that the main Cd 4d peak appears at 11.2 eV, which matches with the reported data of CdS. 44 In addition, we observed that a shoulder appeared at higher binding energy. Further, the features of the Cd 4d peak measured at different take-off angles indicate that the intensity of the main peak gradually decreases and that of the shoulder peak increases with increasing take-off angle.…”
Section: Resultssupporting
confidence: 91%
“…Figure 17 shows the schematic band alignments of the CIGS/ CdS interface for the 30 and 60 nm CdS thin films considering the approximate band bending by Cd diffusion. [43][44][45][46] To investigate the schematic changes in the band alignment by thickness with and without HT, the mean ΔE C change of the band alignment for the 30 nm CdS layer was exhibited. The band alignment here is based on the CBM calculated by UPS and UV measurements as mentioned earlier, so it is approximate alignment compared to the CBM values obtained by IPES measurements.…”
Section: Detailed Mechanism Study and Establishing Optimized Buffer Layer Formation Conditionsmentioning
confidence: 99%
“…However, this is not always the case when the ETL layer is thin enough (e.g., < 5nm), because tunneling effect might assist the current flow through the interface, as Type I heterojunction is prevalent in Cu(In,Ga)Se 2 and Cu 2 ZnSnS 4 solar cells. [ 23–25 ] Type I band alignment can effectively prevent the interface recombination due to a large distance between E c of ETL and E v of perovskite. Nevertheless, it is reported that in‐situ growth of a high band gap interlayer in the HTL/perovskite interface can improve the V oc substantially, which is mainly due to the Type I band alignment formed in the interface.…”
Section: Basic Theory On Interface Engineeringmentioning
confidence: 99%